MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN MELALUI MEDIA GAMBAR PADA ANAK USIA 5 – 6 TAHUN DI PAUD BAHRUL IHSAN KAWASEN - Fatimah, Ade Siti; Hidayat, Yusuf; Herniawati, Ani (Jurnal Intisabi, 2024)
Pre-reading for early childhood is the initial ability for early childhood to recognize sounds, letters, syllables, and words that symbolize them that can be read by early childhood in the form of simple sentences. This study aims to find out how the picture media can help to improve initial reading ability for early childhood aged 5-6 years at PAUD Bahrul Ihsan Kawasen. This study uses a Classroom Action Research (CAR) as the research method. This research was conducted into 2 cycles, at which each cycle refers to four components: planning, acting, observing, and reflexing. The results of the study showed that in cycle I, early childhood’s initial reading ability reached 78% with the achievement of Developing According to Expectation (BSH). Then, in cycle II, early childhood’s initial reading ability increased up to 94% with the achievement of Developing According to Expectation (BSH). Thus, the use of picture media is able to improve early childhood’s initial reading ability at PAUD Bahrul Ihsan Kawasen.